Gambaran Perilaku Wanita Usia Subur Tentang Inspeksi Visual Asam Asetat: IVA, Pengetahuan, Sikap, Wanita Usia Subur - Utari, Luh Sri; Kompiang Sriasih, Ni Gusti; Novya Dewi, I Gusti Agung Ayu (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2025)
Cervical cancer is a malignancy that attacks the cervix or mouth of the uterus. Cervical cancer can be detected early with one of the methods of Visual Inspection of Acetic Acid. This study aims to determine the behavioral description of women of childbearing age about IVA in the Tampaksiring I Gianyar Health Center working area in 2024. This research design is a descriptive survey with a sample size of 74 respondents. The sampling technique used was systematic random sampling. There are two data in this study, namely primary data and secondary data. Primary data for knowledge and attitudes using questionnaire instruments that have been tested for validity and reliability with the results of valid and reliable questionnaires. Secondary data from SIGA BKKBN data in 2024 for IVA actions were checked with a period of a week whether women of childbearing age came to do acetic acid visual inspection examination to Tampaksiring I Health Center. The study was conducted in May 2024. Data analysis used in this study was univariate analysis. The results of this study showed as many as 74.3% had good knowledge about visual inspection of acetic acid, as many as 56.8% of women of childbearing age had a negative attitude about visual inspection of acetic acid, and as many as 89.2% of women of childbearing age did not conduct visual inspection of acetic acid at the public health center. The conclusion of the study shows that most women of childbearing age have a bad attitude about visual inspection of acetic acid in the Tampaksiring I Gianyar Health Center working area in 2024. The health center should improve health education to women of childbearing age proactively about cervical cancer screening with acetic acid visual inspection method.